The use of fixed-term contracts and the labour adjustment in Belgium - Emmanuel Dhyne; Benoit Mahy (National Bank of Belgium, 2009)
This paper aims to document and analyse the use of fixed-term contracts (FTC) and to analyse the dynamics of labour adjustment by type of labour contract at the firm level, drawing on the detailed breakdown of both the labour force and labour entries and exits that are available in the "Belgian Firms' Social Balance Sheets" dataset. It also aims to investigate the structure of labour adjustment costs by type of labour contract, using the methodology proposed by Goux, Maurin and Pauchet (2001). Results first indicate that flexible labour contracts are not only used to facilitate short-term labour adjustment but also as a screening device. The findings also suggest that when a firm decides to introduce flexible labour into its production process, it does also this to meet long-run objectives such as implementing minimising costs innovations. It is further estimated that the introduction of FTCs does not seem to affect the speed of indefinite-term contracts (ITC) adjustment. Our results also tend to indicate that the FTC is a key adjustment variable in response to cost shocks and to unexpected demand fluctuations while, in response to expected fluctuations in output, firms then prefer to adjust their level of permanent employment. Finally, and as far as the structure of labour adjustment costs in Belgium is concerned, the marginal recruitment cost under an ITC represents 12.4% of the marginal termination cost of ITC, while the marginal cost associated with the recruitment under an FTC only accounts for 0.8% of its ITC counterpart
Keywords: J23; J32; J63; J82; 330; labour dynamics; fixed-term contract; indefinite-term contract; agency workers; Befristete Beschäftigung; Arbeitsmarkt; Personalbeschaffung; Kosten; Belgien